POTENSI UMBILICAL CORD BLOOD DERIVED STEM CELLS DALAM MEMPERBAIKI KERUSAKAN OTAK AKIBAT PENYALAHGUNAAN NARKOTIKA - Irfan Hasbullah Putra (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2018)
ntroduce: The prevalence of drug abuse in the world has increased. In Indonesia, Thenumber of cases of narcotics abuse has increased in the last 5 years while thoseincluded in other additives decreased the number of cases. Opiates, one of narcotics,have the most evident addictive effects, involving tolerance, withdrawal, and a high rate of relapse. Beside that, the mechanisms involved in the neurotoxicity of these drugsinclude oxidative stress, apoptosis, mitochondrial dysfunction, and inhibition ofneurogenesis. Neural system is incapable to self-repair and renewal. In contrast, neuralstem cells can repair and treat the neurogical disorders. Stem cells can be self-adaptiveto the host environment providing multi-folded roles, from neuronal protection,neurotrophic effect to direct neuronal replacement to facilitate the repair and regenerative process of the injured CNS following brain damage. Discussion: Human cord bloodstem cell express nestin which effective in promoting differentiation of oligodendrocytes, astroglia, and neurons nd recruit them to repair damaged area in brain caused by drug abuse. Conclusion: Umbilical cord blood derived stem cells can be an alternative,innovative and effective therapy to repair repairing brain demage caused by narcotics abuse